2022
DOI: 10.1007/s11307-022-01793-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis and Analysis of (S)-4-(3-[18F]Fluoropropyl)-L-Glutamic Acid

Abstract: Purpose (S)-4-(3-[18F]Fluoropropyl)-L-glutamic acid ([18F]FSPG) is an L-glutamate derivative used as a PET biomarker to assess intracellular redox status in vivo through targeting of the cystine/glutamate antiporter protein, xc− transporter. In this report, we describe a radiosynthesis of [18F]FSPG for use in PET studies that address specific challenges in relation to the radiotracer purity, molar activity, and quality control testing methods. Procedures T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Radio-HPLC analysis of the produced [ 18 F]FSPG for injection showed > 95% radiochemical purity. In line with previous reporting, the major impurity can be attributed to [ 18 F]Fluoride (Brown et al 2023 ). Further analysis after 8 h confirmed that the product remained stable (Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Radio-HPLC analysis of the produced [ 18 F]FSPG for injection showed > 95% radiochemical purity. In line with previous reporting, the major impurity can be attributed to [ 18 F]Fluoride (Brown et al 2023 ). Further analysis after 8 h confirmed that the product remained stable (Fig.…”
Section: Resultssupporting
confidence: 92%
“…We have achieved the cGMP-compliant automated production of [ 18 F]FSPG with optimal synthesis procedure for both GE TRACERlab™ FXFN and FASTlab™ synthesizer. While several commercially available modules for [ 18 F]FSPG production have been previously published (Koglin et al 2011 ; Kavanaugh et al 2016 ; Mittra et al 2016 ; McCormick et al 2019 ; Shih et al 2020 ; Edwards et al 2021 ; Brown et al 2023 ), our method has consistently produced [ 18 F]FSPG at high radiochemical purity and high molar activity. In particular, our adaptation of the SPE purification method was elegantly simplified in setup and with minimal processing time, making it attractive for centralized and large-scale production of [ 18 F]FSPG at a manufacturing facility.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have achieved the cGMP-compliant automated production of [ 18 F]FSPG with optimal synthesis procedure for both GE TRACERlab ™ FXFN and FASTlab ™ synthesizer. While several commercially available modules for [ 18 F]FSPG production have been previously published ( Brown et al, 2023 ; Edwards et al, 2021 ; Kavanaugh et al, 2016 ; Koglin et al, 2011 ; McCormick et al, 2019 ; Mittra et al, 2016 ; Shih et al, 2020 ), our method has consistently produced [ 18 F]FSPG at high radiochemical purity and high molar activity. In particular, our adaptation of the SPE purification method was elegantly simplified in setup and with minimal processing time, making it attractive for centralized and large-scale production of [ 18 F]FSPG at a manufacturing facility.…”
Section: Discussionmentioning
confidence: 99%
“…Producing radiotracers with highly consistent radiochemical yield and quality is required to bring promising radiotracers from bench to bedside. Although several groups have described automated procedures to produce [ 18 F]FSPG, previous reports were focused on small-scale production (less than 400 MBq of the final product) and with complex modifications of commercially available cartridges ( Brown, Soloviev, & Lewis, 2023 ; Edwards, Greenwood, McRobbie, Khan, & Witney, 2021 ; Kavanaugh et al, 2016 ; Koglin et al, 2011 ; McCormick et al, 2019 ; Mittra et al, 2016 ; Shih et al, 2020 ), making it challenging to directly implement at a manufacturing facility. Here, we report a detailed and highly robust technical protocol to produce the large-scale, cGMP-compliant radiosynthesis of [ 18 F]FSPG using GE TRACERlab ™ FXFN and FASTlab ™ , the most widely used synthesis modules for routine clinical radiopharmaceutical production.…”
Section: Introductionmentioning
confidence: 99%